2019
DOI: 10.1111/jfpp.13999
|View full text |Cite
|
Sign up to set email alerts
|

Effect of air classification processing variables on yield, composition, and certain antinutrients of air‐classified fractions from field peas by response surface methodology

Abstract: The effect of processing parameters of air classification on the yield, composition, and certain antinutritive values of the air‐classified fractions from peas was investigated using response surface methodology. Results indicated that increasing classifier wheel speed increased yield and starch content of starch‐rich fraction, protein, and total dietary fiber (TDF) content of protein‐rich fraction, but reduced yield and starch content of protein‐rich fraction, protein, and TDF content of starch‐rich fraction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
33
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 23 publications
9
33
1
1
Order By: Relevance
“…These observations are expected since increasing rotor speed increased the centrifugal force, resulting in more particles thrown against the cyclone casing and descending to the coarse cyclone. This was in agreement with the results of Wang and Maximiuk who reported that increasing the separating rotor speed increased the yield of coarse fraction for field pea flour . The secondary air stream was used to increase the residence time of particles in the cyclone house.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…These observations are expected since increasing rotor speed increased the centrifugal force, resulting in more particles thrown against the cyclone casing and descending to the coarse cyclone. This was in agreement with the results of Wang and Maximiuk who reported that increasing the separating rotor speed increased the yield of coarse fraction for field pea flour . The secondary air stream was used to increase the residence time of particles in the cyclone house.…”
Section: Resultssupporting
confidence: 92%
“…Increasing the separating rotor speed increased the centrifugal force and brought more particles to end up in the coarse fraction, leading to low fine fraction yield, but high protein concentration in the fine fraction. This is in accordance with the results of Wang and Maximiuk who found that increasing rotor speed resulted in fine fractions of high protein content for field pea flour . Protein‐rich particles were reported to be only 1–3 μm in diameter .…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Protein and starch concentrate from the dehulled pea sample were prepared by air classification process according to Wang and Maximiuk (2019). Dehulled peas were milled using an Alpine 160 Z pin mill (Alpine) at 17,000 rpm.…”
Section: Methodsmentioning
confidence: 99%